Kesiapan Masyarakat dalam Menghadapi Penyakit Pasca Banjir di Dusun Lohgawe Desa Gawerejo Kecamatan Karangbinangun Kabupaten Lamongan - Saputra, Muhamad Ganda; Ummah, Faizatul (UI Scholars Hub, 2021)
Floods cause post-flood diseases including diarrhea, leptospirosis dengue fever, ARI, intestinal worms, skin diseases and various other comorbidities. Objective: This study aims to describe the readiness of the community to face post-flood diseases in Lohgawe Hamlet, Gawerejo Village, Karangbinangun Lamongan District. This study used a descriptive design, with a population of 70 community heads and a sample of 59 community heads. The sampling used is simple random sampling. Collecting data with questionnaire sheets, scoring, coding, tabulating and drawing conclusions with percentages. Based on the results of the study, it was found that most of the readiness of public funds in dealing withpost-flood diseases was moderate, namely 30 respondents or 50.85%, most of the readiness of public transportation in dealing withpost-flood diseases was less, namely 34 respondents or 57.63%, most of the environmental readiness the community in dealing with post-flood diseases is moderate, namely 36 respondents or 61.01%, some of the readiness of community communication tools in dealing with post-flood diseases are moderate, namely 26 respondents or 44.06%, and partly the readiness of health workers in dealing with post-flood diseases is moderate. namely 24 respondents or 40.68%. Efforts to improve community readiness in dealing with post flood disease, the role of health workers is expected to be able to help provide information about post-flood disease problems, how to prevent them and how to handle them, so that people can be prepared in dealing with post-flood diseases.